Comparison of trans fatty acid content in commonly consumed seed oils and commercially refined counterparts - Kabir, Md Alamgir; Lisa, Sharmin Akter; Alam, Md Mahbub; Hossain, Md Kamal; Islam, Sheikh Nazrul; Shaheen, Nazma (Bangladesh Journal of Scientific and Industrial Research, 2025)
Conventional seed oils and their commercially refined counterparts may contain different levels of trans fatty acids (TFA) due to refining and high heat treatment during deodorization. To identify and quantify TFA content in five commonly consumed marketed refined vegetable oils namely refined soybean oil (RSO), refined palm oil (RPO), mustard oil (MO), refined rice bran oil (RRBO), and refined sunflower oil (RSuO) were analyzed. To identify the potential source of TFA, seed extract and crude extract of the studied oil were also analyzed. Among the 57 analyzed samples, the highest TFA was found in RRBO 4.35±3.88% followed by RSO 3.50±1.54%. RSuO and RPO contained TFA within the recommended level of the World Health Organization whereas TFA was identified below the detection limit in MO. Very little TFA was observed in crude palm oil, rice bran, and soybean seed extracted oil, while no TFA was found in mustard and sunflower seed extracted oil. Bangladesh J. Sci. Ind. Res. 60(1), 63-72, 2025